Amazon deforestation reduces precipitation and soybean yields across Southern Brazil - Hao Li; Corey S. Lesk; Lei Zhu; Thomas W. Crowther; Min Chen; Deepak K. Ray; Nathaniel D. Mueller (Proceedings of the National Academy of Sciences, 2026)
Rapid agricultural expansion has driven forest loss worldwide. Deforestation reduces evaporation, potentially decreasing precipitation and crop yields far beyond agricultural frontiers. Here, we quantified the teleconnection impacts of Amazon deforestation on precipitation and soybean yields across Brazil during 1982–2018, using a Lagrangian moisture tracking model. Our analysis indicates that tree evaporation contributes one-third of growing-season precipitation, yet recent deforestation decreased seasonal precipitation by 6 to 30% across Brazilian soybean states, with replacement land covers providing limited compensation for the losses. Although precipitation declines were most pronounced near Amazonian deforestation, the largest yield reductions (227 kton, or ∼ 6% loss) occurred in the southern state of Rio Grande do Sul. Cumulatively, deforestation-driven precipitation declines resulted in a total soybean production loss of ∼ 700 kton. These findings reveal that expanding agriculture into forests undermines yields in established croplands, potentially creating a feedback where yield losses drive demand for additional forest clearing. Under continued deforestation and climate change, this feedback is likely to intensify, threatening Brazilian rainfed agriculture into the future.